Réponses

2014-09-03T21:50:26+02:00
A = 8/7 x 15/12 - 4/7
A = 120/84 - 4/7
A = 120/84 - 4 x 12 / 7 x 12
A = 120/84 - 48/84
A = 72/84
A = 12 x 6 / 12 x 7
A = 6/7

B = 3 - 2 x 5/3
B = 3 - 10/3
B = 3 x 3 / 1 x 3 - 10/3
B = 9/3 - 10/3
B = - 1/3

C = 3/5 - 1/7 x 21/9 - 12/20
C = 3/5 - 2/63 - 12/20
C = 3 x 252 / 5 x 252 - 2 x 20 / 63 x 20 - 12 x 63 / 20 x 63
C = 756/1260 - 40/1260 - 756/1260
C = - 40/1260
C = 20 x - 2 / 20 x 63
C = - 2/63

D = 5/6 + 7/9
D = 5 x 3 / 6 x 3 + 7 x 2 / 9 x 2
D = 15/18 + 14/18
D = 29/18

E = 50/14 x 7/15
E = 350/210
E = 70 x 5 / 70 x 3
E = 5/3

F = 11 - 7/3 x 2/5 + 8/5
F = 11 - 14/15 + 8/5
F = 11 x 15 / 1 x 15 - 14/15 + 8 x 3 / 5 x 3
F = 165/15 - 14/15 + 24/15
F = 175/15
F = 5 x 35 / 5 x 3
F = 35/3

G = (2 + 7/3) ( (1 - 8/5)
G = (2 x 3 / 1 x 3 + 7/3) (1 x 5 / 1 x 5 - 8/5)
G = (6/3 + 7/3) (5/5 - 8/5)
G = 13/3 x - 3/5
G = - 39/15
G = 3 x - 13 / 3 x 5
G = - 13/5

H = 5 - 3/4
H = 5 x 4 / 1 x 4 - 3/4
H = 20/4 - 3/4
H = 17/4

I = 7/3 - 2/9 x 3/2
I = 7/3 - 6/18
I = 7 x 6 / 3 x 6 - 6/18
I = 42/18 - 6/18
I = 36/18
I = 18 x 2 / 18 x 1
I = 2/1
I = 2

J = 3/4 - 1/2 + 13/12
J = 3 x 3 / 4 x 3 - 1 x 6 / 2 x 6 + 13/12
J = 9/12 - 6/12 + 13/12
J = 16/12
J = 4 x 4 / 4 x 3
J = 4/3

K = 3/8 x 16/15
K = 48/120
K = 24 x 2 / 24 x 5
K = 2/5

L = 2/3 : 5/7
L = 2/3 x 7/5
L = 14/15

M = 4 - 3 x 2/5
M = 4 - 6/5
M = 4 x 5 / 1 x 5 - 6/5
M = 20/5 - 6/5
M = 14/5

N = (23/17 - 19/51) : (- 4/3)
N = (23 x 3 / 17 x 3 - 19/51) : - 4/3
N = (69/51 - 19/51) : - 4/3
N = 50/51 x 3/4
N = 150/204
N = 6 x 25 / 6 x 34
N = 25/34

P = 5/3 + 3/5 x 25/6
P = 5/3 + 75/30
P = 5 x 10 / 3 x 10 + 75/30
P = 50/30 + 75/30
P = 125/30
P = 5 x 25 / 5 x 6
P = 25/6

Q = 5 : 35/3
Q = 5 x 3/35
Q = 15/35
Q = 5 x 3 / 5 x 7
Q = 3/7

R = 17 - 15 x 3/20
R = 17 - 45/20
R = 17 x 20 / 1 x 20 - 45/20
R = 340/20 -45/20
R = 295/20
R = 5 x 59 / 5 x 4
R = 59/4

S = (5/7  - 3/2) : (3/7 + 1/49)
S = (5 x 2 / 7 x 2 - 3 x 7 / 2 x 7) : (3 x 7 / 7 x 7 + 1/49)
S = (10/14 - 21/14) : (21/49 + 1/49)
S = - 11/14 : 22/49
S = - 11/14 x 49/22
S = - 539/308
S = 77 x - 7 / 77 x 4
S = - 7/4

T =        1____
     7/10 - 9/13
T =                        1___________
       7 x 13 / 10 x 13 - 9 x 10 / 13 x 10
T =             1______
       91/130 - 90/130
T = 1 : 1/130
T = 1 x 130/1
T = 130/1
T = 130

U = (4/7)² - 5/3 x 12/7
U = (4²/7²) - 60/21
U = 16/49 - 60/21
U = 16 x 21 / 49 x 21 - 60 x 49 / 21 x 49
U = 336/1029 - 2940/1029
U = - 2604/1029
U = 21 x - 124/ 21 x 49
U = - 124/49

V = 8/15 : 4/9
V = 8/15 x 9/4
V = 72/60
V = 12 x 6 / 12 x 5
V = 6/5

W = 1 + 2/5
         7/2 - 2
W = 1 x 5 / 1 x 5 + 2/5
       7/2 - 2 x 2 / 1 x 2
W = 5/5 + 2/5
       7/2 - 4/2
W = 7/5 : 3/2
W = 7/5 x 2/3
W = 14/15

X = 1 + 1/3 - 1/2
       2 + 3/4 + 1/3
X =    1 x 6 / 1 x 6 + 1 x 2 / 3 x 2 - 1 x 3 / 2 x 3__
       2 x 12 / 1 x 12 + 3 x 3 / 4 x 3 + 1 x 4 / 3 x 4
X =      6/6 + 2/6- 3/6___
     24/12 + 9/12 + 4/12
X = 5/6 : 37/12
X = 5/6 x 12/37
X = 60/222
X = 6 x 10 / 6 x 37
X = 10/37

Y = - 3/4 - ( 1 - 3/4) + 2 (3 + 5/6)
Y = - 3/4 - (1 x 4 / 1 x 4 - 3/4) + 2 (3 x 6 / 1 x 6 + 5/6)
Y = - 3/4 - (4/4 - 3/4) + 2 (18/6 + 5/6)
Y = - 3/4 - 1/4 + 36/6 + 5/6
Y = - 3 x 6 / 4 x 6 - 1 x 6 / 4 x 6 + 36 x 4 / 6 x 4 + 5 x 4 / 6 x 4
Y = - 18/24 - 6/24 + 144/24 + 20/24
Y = 140/24
Y = 4 x 35 / 4 x 6
Y = 35/6

Z = 2/3 (3/2 - 3) - 4/5 (5/4 - 5)
Z = 2/3 (3/2 - 3 x 2 / 1 x 2) - 4/5 (5/4 - 5 x 4 / 1 x 4)
Z = 2/3 (3/2 - 6/2) - 4/5 (5/4 - 20/4)
Z = 2/3 (- 3/2) - 4/5 (- 15/4)
Z = - 6/6 + 60/20
Z = - 6 x 20 / 6 x 20 + 60 x 6 / 20 x 6
Z = - 120/120 + 360/120
Z = 240/120
Z = 120 x 2 / 120 x 1
Z = 2/1
Z = 2